CP-021 Clinical experience with baclofen in alcohol dependence treatment. (25th February 2017) - Néant, N; Massa, F; Tannous, M; Van Cappel De Premont, C; Orabona, V; Grassi, J
Abstract : This abstract was published in error and withdrawn at the author's request.